The TDR helicopter concept : design and integration of the Ljungström turbine - Buysschaert, F.; Newman, S.; Walker, S.; Hendrick, P.; Antoine, H. (My University, 2015)
This paper examines the design of a rotor embedded Ljungström turbine (RELT) and its integration in the TDR helicopter cycle, with the objective to maximise the performance gain of the TDR helicopter with respect to conventional single rotor helicopters. For this purpose, a RELT turbine model is discussed briefly and applied to a 500 kg VLR- and a 10 metric ton NH-90-class TDR helicopter in nominal operation conditions ISA SLS. In this study, the coefficient of performance margin is vital. The VLR-class TDR helicopter, using either an Avgas or a Diesel reciprocating engine of approximately 90 kW, exhibits a performance gain of circa 10% over the conventional helicopter. The NH-90-class TDR helicopter benefits from an impressive coefficient of performance margin of 47% while using a turbofan with a thrust potential of 22.5 kN, which makes the concept attractive in the heavy helicopter category. For both configurations, a RELT geometry is proposed yielding adequate turbine polytropic efficiencies between 85% and 90%.
Keywords: Engines & Propulsion